Assessment of genetically modified cotton GHB811 for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐ES‐2018‐154). (16th August 2021) - ,; Naegeli, Hanspeter; Bresson, Jean Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: Cotton GHB811 was developed to confer tolerance to glyphosate and HPPD inhibitor herbicides. The molecular characterisation data and bioinformatic analyses do not identify issues requiring food/feed safety assessment. None of the identified differences in the agronomic/phenotypic and compositional characteristics tested between cotton GHB811 and its conventional counterpart needs further assessment, except for % lint, lint length and dihydrosterculic acid, which do not raise nutritional and safety concerns. The GMO Panel does not identify safety concerns regarding the toxicity and allergenicity of the 2mEPSPS and HPPD W336 proteins as expressed in cotton GHB811 and finds no evidence that the genetic modification would change the overall allergenicity of cotton GHB811. In the context of this application, the consumption of food and feed from cotton GHB811 does not represent a nutritional concern in humans and animals. The GMO Panel concludes that cotton GHB811 is as safe as the conventional counterpart and non‐GM cotton reference varieties tested, and no post‐market monitoring of food/feed is considered necessary. In the case of accidental release of viable cotton GHB811 seeds into the environment, this would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of cotton GHB811. The GMO Panel concludes that cotton GHB811 is as safe as its conventional counterpart and the tested non‐GM cotton reference varieties with respect to potential effects on human and animal health and the environment.